3D printing of green and environment-friendly rGO@ZnO/GP for removal of methylene blue from wastewater. (March 2023) - Liu, Xuehui; Ma, Siqi; He, Peigang; Wang, Meirong; Duan, Xiaoming; Jia, Dechang; Colombo, Paolo; Zhou, Yu
Abstract: In this work, we report the fabrication of geopolymer materials containing different amounts of reduced graphene oxide loaded on zinc oxide (rGO@ZnO/GP) to be used as efficient photocatalysts for the degradation of methylene blue (MB). The synergistic effects of adsorption and photodegradation resulted in a 92.56% removal efficiency of MB within 30 min by a geopolymer containing 56%rGO@ZnO (56%rGO@ZnO/GP). The results showed that the geopolymer matrix provided a reusable carrier for rGO@ZnO, and the presence of rGO could promote the migration of photogenerated electrons and hinder the recombination of charges, thereby enhancing the photocatalytic activity. The best performing material (56%rGO@ZnO/GP) was also used to 3D print a scaffold using Direct Ink Writing technology. The 3D printed 56%rGO@ZnO/GP was also an efficient photocatalyst for the degradation of MB, and the use of a structured catalyst facilitates the recovery of the active material. This work can provide a way for preparing efficient and environmentally friendly photocatalysts. Graphical abstract: Image 1 Highlights: Novel rGO@ZnO/GP photocatalysts were designed. The photocatalytic activity of rGO@ZnO/GP was tested and the photocatalytic mechanism was investigated. rGO@ZnO/GP was able to decompose MB through the synergistic effect of adsorption and photocatalysis. The 3D-printed rGO@ZnO/GP could be recycling and reuse.